The Role of Digital Libraries in Sustaining Access to Information in Context to Indian Government Publications - Jain, Ms. Chhavi (IJRDO- Journal of Educational Research, 2016)
A Digital Library is a set of services and technologies that provide the means to collect, manage, access, disseminate, and preserve digital materials produced in any digital format. Digital Library disseminates rich source of digitized materials drafted and published by any organization or individual. While most digital libraries are based at educational institutions like colleges and universities, they also exist in the governmental agencies, museums, corporations and other organizations. In India major R& D institutes and Academic Institutes provide Digital Library service to its clientele. This technology offers organizations and researchers to deposit their work which facilitates the target audience to access the publications via digital form. Digital Libraries are becoming an increasingly important type of special resource and service offered by any institute. The essence of Digital Library is to make publications to be freely available on internet. This initiative was directed to have an increased visibility of the published documents; further this will generate good deal of enthusiasm in users. The content of a Digital Library may include many different types of resources: published books and journal articles, dissertations, other types of academic publications, and various types of unpublished articles, such as journal preprints, technical reports, research progress reports, courseware, and other gray literature audio and video recordings in born digital and digitized manner. The sharing of knowledge may lead to further development in the same discipline or related disciplines. Digital Library is now becoming a platform for the sharing of knowledge.